ChemInform Abstract: Food Wastes Conversion to Products for Use in Chemical and Environmental Technology, Material Science and Agriculture. Issue 4 (January 2015) - Montoneri, Enzo; Prevot, Alessandra Bianco; Avetta, Paola; Arques, Antonio; Carlos, Luciano; Magnacca, Giuliana; Laurenti, Enzo; Tabasso, Silvia
Abstract Review: 108 refs.